FORWARD--Freight Options for Road, Water, and Rail for the Dutch : final report - Hillestad, R. J. (Richard John), 1942-; Walker, Warren E.; Carrillo, M. J. (Manuel J.), 1949-; Bolten, J. G. (Joseph George), 1944-; Twaalfhoven, Patricia G. J.; Riet, Odette van de.; Rand eBooks (Santa Monica, CA : RAND, 1996)
This report describes a major transportation research study that examined the benefits and costs of a broad range of policy options for mitigating negative impacts of the expected growth in Dutch road freight transport while retaining economic benefits. The study's key findings were: the most cost-effective policy options ("tactics") are those that improve road freight transport efficiency, tactics that mitigate transport problems at their source are sometimes cost-effective and complement the transport efficiency improvements, tactics based on shifting freight from road to other transport modes are not cost-effective if the other modes' service characteristics are not improved, the promising tactics' effects on the economy are usually small. The methodology employed was a structured policy-analysis approach developed to handle situations involving complex systems and competing interest groups. Impacts of the various policy options were estimated using a model (PACE-FORWARD) also useful for reevaluating policy options as projections change and/or more data become available. Existing Dutch and international research, data, and models were used extensively, as was input from policymakers and other stakeholders.
"RAND European-American Center for Policy Analysis."
Includes bibliographical references (p. 193-198).
Also available on the internet via WWW in PDF format.
Keywords: Freight and freightage -- Netherlands; Transportation -- Decision making -- Mathematical models; Transportation -- Forecasting -- Mathematical models; Electronic books